An Analysis of Code Mixing Used by Teachers in Teaching English at SMPN 34 Padang - DMS, Mellynia Aprilia; Oktoviandry, Rifki (Universitas Negeri Padang, 2024)
This research aimed to know the type of code mixing, the dominant type of code mixing and reasons why the teachers used code mixing in the teaching learning process at SMPN 34 Padang. The research methodology that used in this research was descriptive qualitative method. The subjects of this research were English teacher at SMPN 34 Padang. This research used observation and interview in collecting the data. The result showed that there were three types of code mixing that used by English teacher in teaching learning process, namely intra sentential code mixing, intra lexical code mixing and involving change of pronunciation. Intra sentential code mixing was the dominant type that used by English teachers in teaching learning process, which is 104 utterances included intra sentential code mixing, 15 utterances included intra lexical and 11 utterances included involving change of pronunciation. While the reasons of the teachers used code mixing in teaching learning process were Repetition for clarification, Expressing affection, emotion, or attitude and Lack of proficiency or lexical gap.